Can barely winning lead to losing? Evidence for a substantial gender gap in psychological momentum - Mario Lackner; Michael Weichselbaumer (Johannes Kepler University of Linz, Department of Economics, 2021)
We use data from professional tennis to measure the causal effect of past on current performance for women and men. Identification relies on exogenous shocks to the probability of facing a contested game, which is a previous stage of competition with strong resistance. We find fundamental gender differences: whereas men's performance is unaffected by previously facing and winning a contested game, women experience a sizeable deterioration of performance after barely winning the previous stage. This result is linked to gender differences in psychological momentum. Detailed analysis reveals heterogeneous effects by experience, ability and contest progression.
Keywords: J16; M52; 330; Performance feedback; relative performance; process feedback; gender differences; psychological momentum